Investigating the Naming Pattern of Places from the Perspectives of Sikkanese: An Anthropolinguistics Study - Janggo, Wendelinus; URAN, MARIA ARNOLDIANA DADJAN URAN (Bina Nusantara University, 2023)
The research investigated the naming pattern of places from the perspective of Sikkanese. Specifically, it was an attempt to describe (a) the place naming pattern in Sikka regency, (b) the meaning behind naming from the perspective of Sikanese, and (c) the relationship between the naming pattern and its meaning and its cultural values. The research used anthropolinguistic theory, toponymy, meaning, and cultural values. It used in-depth interview techniques as its main source and some previous literature studies as its secondary source. The analysis method used was the descriptive qualitative method. The results show that the lingual unit of naming pattern in Sikka regency covers a word, a combination of more than two words, and a noun phrase (Descriptive Adjective+Noun and Noun adjunct+ Noun). Meanwhile, in terms of the toponymy aspect, the place naming pattern in Sikka regency consists of three fundamental aspects, such as (1) manifestation aspect, (2) social aspect, and (3) cultural aspect. Besides that, the researchers also notice an interesting phenomenon where there is a combination between manifestation aspect (flora) and cultural aspect (myths) in the naming pattern of several places. Meanwhile, in terms of meaning, it is found that each place in Sikka regency has its own peculiar characteristics that closely relate to their history, beliefs, folklore, legend, naturalÂ surroundings, and their understanding of something in perceiving the world. In addition, the historical meaning also plays a vital role when it is used as a reminder for the present generation about their cultural heritage from their past generations.